Cultural Hegemony in the Grade XII Islamic Religious Education Textbook Under the Merdeka Curriculum: A Critical Discourse Analysis - Thoyibah Thoyibah; Muhlisin Muhlisin; Slamet Untung; Muhammad Jaeni; Moh. Muslih (Jurnal Pendidikan Terapan, 2026)
Purpose: This study examines cultural hegemony in the Grade XII Islamic Religious Education (PAI) textbook under the Merdeka Curriculum from the perspectives of multicultural education and critical theory. It focuses on the role of textbooks in shaping religious knowledge and cultural representation in Indonesia’s multicultural context. Methods: A qualitative design using Norman Fairclough’s three-dimensional Critical Discourse Analysis was applied to one officially published Grade XII PAI textbook. The analysis covered textual narratives, visual representations, illustrations, and learning activities through the dimensions of text, discursive practice, and social practice. Findings: The textbook predominantly presents religious knowledge through centralized and normative narratives, while local Islamic traditions, interpretive plurality, and socio-cultural diversity receive limited representation. The discourse privileges standardized religious perspectives and reinforces dominant religious narratives. Conclusion: The textbook reflects cultural hegemony by privileging dominant religious interpretations and limiting multicultural perspectives. This indicates the need for more plural theological views, stronger representation of local Islamic traditions, and more inclusive textbook discourse. The findings are limited to the analyzed Grade XII textbook. Research Implications: Curriculum developers, textbook authors, educators, and policymakers should integrate multicultural education principles more fully into Islamic Religious Education materials to support inclusive and culturally responsive learning. Originality: This study integrates Fairclough’s Critical Discourse Analysis, Gramsci’s theory of cultural hegemony, and multicultural education to examine ideological representation in an official PAI textbook and propose a framework for more inclusive learning materials.